Efektivitas Program Keluarga Berencana di Kota Pekanbaru - Syarifah Salwa Azzahra; Mimin Sundari (Peneliti.net, 2022)
Policies in Indonesia to reduce fertility rates in order to improve family welfare are carried out through the Family Planning Program. Family Planning (KB) according to Law Number 52 of 2009 concerning Population Development and Family Development is an effort to regulate the birth of children, the ideal distance and age of childbirth, regulate pregnancy, through promotion, protection, and assistance in accordance with reproductive rights to create a quality family. The Pekanbaru City Government continues to strive to suppress the high rate of population growth by conducting a family planning program under the auspices of the Department of Population Control and Family Planning (Disdalduk KB). The purpose of this study was to determine the effectiveness and constraints in the implementation of the Family Planning Program in Pekanbaru City. The results of the study indicate that the Family Planning Program in Pekanbaru City has been running effectively, but some improvement efforts need to be made. The obstacles to implementing the family planning program are the limited number of field officers and limited socialization due to low community participation.